Surgical margins and oncologic outcomes of tumour-related hemipelvectomies for bone and soft tissue tumours in HUSM - Sharifudin, Mohd Ariff; Wan, Zulmi; Wan Ismail, Wan Faisham Numan; Mat Zin, Nor Azman; Mohamed Amir, Nawaz Hussain (2012)
Introduction: Safe surgical margins are difficult to achieve when performing surgical resections for bone and soft tissue tumours involving the pelvis. We evaluated whether safe surgical margins could be achieved and if oncological outcomes could be predicted based on the microscopic marginal status. Patients and Methods: We analyzed 64 cases of pelvic tumours of various types underwent hemipelvectomy in HUSM throughout a 10-year between year 2001 till 2010. Various clinicopathologic factors were analyzed in relation to the oncologic outcomes of local recurrence, distant metastasis, and disease-specific death. Results: Mean age at time of surgery was 39.84 years (range 8 to 79 years). Majority of cases were primary tumours (76.56%). Chondrosarcoma (n = 14) and osteosarcoma (n = 13) were the most common diagnoses. There were 10 cases of stage IB tumour, 4 cases of stage IIA, 19 cases of stage IIB, and 22 cases of stage III. Twenty-three patients underwent external hemipelvectomy and 35 patients subjected for internal hemipelvectomy of various types of resections. Majority (71.88%) of cases were treated with curative intention. Fourteen of 37 cases (37.84%) attempted for wide resection came back as having positive microscopic margins. Incidence of positive microscopic margin was higher in cases with wide contaminated margins, in which 56.25% of cases had a positive microscopic margin. Our results showed local and distant recurrence rate were higher when margins were positive. But paradoxically the disease-specific death rate was lower in cases with positive margins. Conclusion: Microscopic margin was a prognostic factor for all three primary endpoints of this study, but was not statistically significant. Other prognostic factors for survival include stage of tumour, histological diagnosis, and types of surgery.